2014
DOI: 10.1136/oemed-2013-101754
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone use and brain tumours in the CERENAT case-control study

Abstract: These additional data support previous findings concerning a possible association between heavy mobile phone use and brain tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(91 citation statements)
references
References 44 publications
4
81
0
6
Order By: Relevance
“…Using the mobile phone with weak signal coverage was associated with diagnosis of anxiety and irritability. Coureau et al 37 found a statistically significant association between using the mobile phone for more than two hours a day and brain tumors, concluding that the data reinforce the results of previous studies on intensive use of mobile phones and such tumors. Martin et al 38 conducted measurements of the spectra of non-ionizing electromagnetic radiations in São José dos Campos and Taubaté, São Paulo State, Brazil, indicating that the sources with the heaviest pollution in frequencies ranging from 1MHz to 9.4GHz were mobile phones and VHF.…”
Section: In Areas Aroundsupporting
confidence: 81%
“…Using the mobile phone with weak signal coverage was associated with diagnosis of anxiety and irritability. Coureau et al 37 found a statistically significant association between using the mobile phone for more than two hours a day and brain tumors, concluding that the data reinforce the results of previous studies on intensive use of mobile phones and such tumors. Martin et al 38 conducted measurements of the spectra of non-ionizing electromagnetic radiations in São José dos Campos and Taubaté, São Paulo State, Brazil, indicating that the sources with the heaviest pollution in frequencies ranging from 1MHz to 9.4GHz were mobile phones and VHF.…”
Section: In Areas Aroundsupporting
confidence: 81%
“…In the Korean study, significant increases for acoustic neuroma occurred with >2,000 cumulative hours of use when compared to less (7), and in the Swedish study for >2,300 h of cumulative use (8). In three studies, increased risks for meningioma were also found at the highest cumulative hours of use (5,6,9).…”
Section: Introductionmentioning
confidence: 85%
“…The definition of ̔regular use̓ (at least once a week, for 6 months or more) during a period of rapidly increasing mobile phone use resulted in an average use time of ~6 years. Both the INTERPHONE Study Group (5), and Coureau et al (6) used this definition of ̔regular use.̓ in the past few years a number of investigations have included those who have used phones for a decade or longer. in this report we identify and evaluate all case-control studies that incorporate decade-long use of mobile phones to provide a more complete picture of their potential impacts on public health.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations